Maximizing modulation contrast of KTN electro-optic modulator. (February 2022) - Lv, Xiaolei; Zhao, Jiguang; Wang, Xuping; Du, Xiaoping; Liu, Bing; Song, Yishuo; Chen, Hang
Highlights: A novel scheme to maximize the modulation contrast based on the transmittance derivative function model is proposed. The proposed scheme can solve the optimization deviation of the optimization modulation contrast method based on 50% transmittance point for KTN electro-optic modulator. By using the optimal modulation point selected by the proposed method in this paper, the maximum modulation contrast can reach 0.106 and 0.05 at 1 kHz and 500 kHz, which is 3.5 times and 2 times of the traditional method based on 50% light transmittance. Abstract: The KTa1-x Nbx O3 (KTN) electro-optic modulator (EOM) is extensively applied to laser three-dimensional imaging and other fields, and optimizing its modulation contrast is essential for improving its modulation performance. It is generally considered that the modulator achieves optimal modulation contrast when its transmittance is 50%; however, the dielectric constant does not change with the electric field. Instead, the dielectric constant of a KTN crystal has a dynamic response under an electric field, which causes deviations in optimization. This study investigates the dynamic response of the dielectric constant to an electric field at low and high frequencies, and the maximizing modulation contrast method, which is based on the transmittance derivative function, is proposed. In the verification experiment, the proposed optimization method is used to achieve a maximum modulation contrast of 0.106 when the AC electric field is 320 V/m at a frequency of 1 kHz. The bias electric field is 95.4 kV/m, which is 3.5 times that of the 50% transmittance point. Additionally, when the AC electric field is 320 V/m at 500 kHz and the bias electric field is 87.8 kV/m, a maximum modulation contrast of 0.05 is achieved, which is double that of the 50% transmittance point.